Effect of seepage on river bank stability - Nandakumar Narasimhan (2009)
An experiment- based study was conducted in a laboratory flume to investigate the correlation between river bank stability and the erosion forces of seepage under unidirectional current. The study involved the collapse of a bank slope made up of a non cohesive soil (sand) using only the channel flow and ground water flow as erosion forces. Whereas most studies hitherto have focused on the two forces individually (i.e. seepage and current effects separately), this study combined the two forces and studied their combined effect on the failure of the slope. The dimensionless Reynolds number for bed shear stress was plotted against the safety factor for the slope using an analytical expression. It was found that an increased channel flow velocity (hence an increased shear stress and shear velocity) facilitated the collapse of the slope and caused it to collapse at a lower hydraulic gradient than one with very slow flow velocity. However there exists a certain critical value for the Reynolds number beyond which the fluvial erosion forces become significant in causing slope failure. The analytical expression that was determined for submerged slope stability fails at higher flow velocities as it gives a higher factor of safety when it was experimentally observed that the slope failed at lower hydraulic gradients.